PELATIHAN PEMBELAJARAN BERBASIS TEKNOLOGI DIGITAL BAGI GURU TINGKAT MADRASAH IBTIDAIYAH - Muhamad Zaini; Muhamad Nasrulloh; Amelia Nur Baiti; Citra Kurniawati (BHAKTI: JURNAL PENGABDIAN DAN PEMBERDAYAAN MASYARAKAT, 2026)
This Community Service (PkM) activity is motivated by the limited utilization of digital technology in developing learning media within the Madrasah Ibtidaiyah (MI) environment, particularly at MI Nurul Jadid Kolomayan, Wonodadi Blitar. In the context of the Merdeka Curriculum, which emphasizes differentiated learning and technology utilization, teachers at MI Nurul Jadid Kolomayan Wonodadi Blitar face challenges in designing attractive, interactive media that meets students' needs. Therefore, this training program is designed to enhance teachers' competence in designing and developing digital technology-based learning media such as Canva, interactive PowerPoint, Quizizz, and other simple applications. The implementation method employs a participatory approach, intensive mentoring, and hands-on practice that actively involves teachers as subjects. This activity aims not only to increase knowledge and technical skills but also to build positive attitudes toward the adoption of digital technology in learning. The training results show a significant improvement in teachers' understanding of digital media design principles and their ability to independently produce learning media. Thus, this activity is expected to strengthen an innovative learning ecosystem and support the enhancement of teacher competence and educational quality at the madrasah ibtidaiyah level. The sustainability of this program will be directed toward strengthening digital-based teacher learning communities and cross-madrasah collaboration.